2012
DOI: 10.1016/j.bjid.2012.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Desmodus rotundus and Artibeus spp. bats might present distinct rabies virus lineages

Abstract: In Brazil, bats have been assigned an increasing importance in public health as they are important rabies reservoirs. Phylogenetic studies have shown that rabies virus (RABV) strains from frugivorous bats Artibeus spp. are closely associated to those from the vampire bat Desmodus rotundus, but little is known about the molecular diversity of RABV in Artibeus spp. The N and G genes of RABV isolated from Artibeus spp. and cattle infected by D. rotundus were sequenced, and phylogenetic trees were constructed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
1
15
0
3
Order By: Relevance
“…In the present study, eight isolates were genetically characterized as the lineage circulating in D. rotundus (related to AgV3), which is now known to very probably consist of two distinct yet phylogenetically very close genetic lineages (Brandão et al., ; Shoji et al., ; Kobayashi et al., ; Albas et al., ; Fahl et al., ) maintained in independent epidemiological cycles by D. rotundus and the fruit‐eating bat Artibeus lituratus .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In the present study, eight isolates were genetically characterized as the lineage circulating in D. rotundus (related to AgV3), which is now known to very probably consist of two distinct yet phylogenetically very close genetic lineages (Brandão et al., ; Shoji et al., ; Kobayashi et al., ; Albas et al., ; Fahl et al., ) maintained in independent epidemiological cycles by D. rotundus and the fruit‐eating bat Artibeus lituratus .…”
Section: Discussionmentioning
confidence: 86%
“…In the last few years, the importance of Artibeus spp in public health has increased because of the growth in the numbers of these bats in urban areas; furthermore, the fact that they share roosts with D. rotundus (Uieda et al., ; Cunha et al., ; Sodré et al., ) means that these species require special attention. When dogs and cats are infected by bats, the transmitter is generally not known at first, and the real source of the infection can only be established by characterization of the lineages responsible for the infection (Fahl et al., ). However, the fragment of the N gene analysed in the present study is not large enough to differentiate between these two bat lineages and characterize precisely the source of infection as we analysed 193‐bp fragment while Fahl et al.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that 33.3% of the samples from domestic canines with confirmed rabies were found in varieties compatible with AgV3 from VBs. However, it is worth mentioning that the antigenic and genetic characterizations do not indicate the attacking bat species (Castilho et al., ; Fahl et al., ; Kobayashi et al., ). According to Schneider et al.…”
Section: Discussionmentioning
confidence: 99%
“…Mediante el análisis de 35 aislamientos del RABV provenientes del Estado de São Paulo, Fahl et al (2012) observaron diferencias entre linajes genéticas basándose en secuencias parciales de los genes N y G relacionadas con murciélagos D. rotundus y Artibeus spp., los cuales usualmente, pertenecen a la variante antigénica AgV3.…”
Section: Caracterización Genética De Aislamientos Del Rabv En Brasilunclassified